Daily Variability in Sedentary Behaviour and Physical Activity Responsiveness in Older Women - Dale M. Grant; David J. Tomlinson; Kostas Tsintzas; Gladys L. Onambele-Pearson (Sensors)
Free-living physical behaviour (PB), from sedentarism through to vigorous physical activity (PA), is increasingly studied due to its links to health outcomes. However, it remains unclear whether pre-existing day-to-day regularity in certain PB patterns influences intervention responsiveness. Therefore, this study hypothesized that (1) inter-day variability in certain PBs would decrease following a sedentary behaviour (SB) reduction intervention, and (2) those with high inter-day variability (low regularity) at baseline would be less likely to alter their behaviour compared to those with low inter-day variability (high regularity). Thirty-six older women (73 ± 5 years) were allocated to one of three groups: (1) daily SB fragmentation (SBF) (n = 14), (2) single daily bout of continuous light-intensity PA/LIPA (n = 14), or (3) control (n = 8), where no instructions vis-à-vis altering daily physical activity or sedentary behaviour were given. PB was objectively assessed (weeks 0 and 8) using three-dimensional accelerometry. Participants (48% of the study sample) with high regularity at baseline (<25th sample percentile for SB and PA bout length), showed greater SB reduction, and increased average PA bout length (p < 0.05) at week 8. These findings suggest that baseline regularity in physical behaviour may enhance intervention responsiveness. This aligns with theories of habit formation and self-regulation, indicating that personalised interventions would benefit a wider range of populations.